Mortality associated with early changes in ARDS severity in COVID–19 patients – Insights from the PRoVENT–COVID study - Michiel T.U. Schuijt (2022)
Purpose: We investigated changes in ARDS severity and associations with outcome in COVID–19 ARDS patients. Methods: We compared outcomes in patients with ARDS classified as ‘mild’, ‘moderate’ or ‘severe’ at calendar day 1, and after reclassification at calendar day 2. The primary endpoint was 28–day mortality. We also identified which ventilatory parameters had an association with presence of severe ARDS at day 2. We repeated the analysis for reclassification at calendar day 4. Results: Of 895 patients, 8.5%, 60.1% and 31.4% had mild, moderate and severe ARDS at day 1. These proportions were 13.5%, 72.6% and 13.9% at day 2. 28–day mortality was 25.3%, 31.3% and 32.0% in patients with mild, moderate and severe ARDS at day 1 (p = 0.537), compared to 28.6%, 29.2% and 44.3% in patients reclassified at day 2 (p = 0.005). No ventilatory parameter had an independent association with presence of severe ARDS at day 2. Findings were not different reclassifying at day 4. Conclusions: In this cohort of COVID–19 patients, ARDS severity and mortality between severity classes changed substantially over the first 4 days of ventilation. These findings are important, as reclassification could help identify target patients that may benefit from alternative approaches.